Determinants of bank's financing choices under capital regulation - Vanesa Llorens; Alfredo Martin-Oliver (SERIEs - Journal of the Spanish Economic Association, 2017)
This paper analyzes the financing choices of banks under capital regulation during the expansion period that preceded the crisis. We use data from Dealogic on the issuances of financial instruments of Spanish banks to test whether financing choices respond to predictions derived from the corporate finance theory and/or to capital regulation. We find that banks financed their exponential growth with debt instruments and covered the additional regulatory capital requirements from higher risk-weighted assets with the issuance of hybrid instruments. We also find that banks choose the financial instruments that minimize asymmetric information costs.
Keywords: G21; 330; Banks; Capital regulation; Financing choices; Informational asymmetries; Financial markets